أهميت النقل الدولي في نحسين أداء خدمات اللوجستيك في الجزائر - عين سمن, سعيدة (My University, 2018)
Logistics has become an important function ,of a productive and commercial enterprise ,in terms of material needs including supply, production, distribution, and flow of information. Among the main logistics activities, transportation is the main engine of logistics ,for business organizations and the quality of transport services, It adds value to goods or products by providing spatial temporal benefit, since the cost of transport constitutes a large proportion of the total cost of business This has led to the interest of the various establishments and strategies, the supply of the transport function and the attempt to find solutions to the problem ,of pollution caused by transportation
Keywords: النقل الدولي - أداء خدمات- اللوجستيك في الجزائر